Sensory Marketing – Sensory Communication and Its Social Perception - Koszembar-Wiklik, Małgorzata (Communication Today, 2025)
In the past few years, sensory marketing has been developing dynamically. Companies, in search of new methods of reaching the customer, refer to all of their senses. The business is more and more aware of the effectiveness of the impact that sensory marketing has. Especially large enterprises, having a network of points of sale, use this method of manipulating customers’ emotions. Malls are one of such places where sensory marketing is being used on a large scale. The consumer who engages more senses to assess the product offer of the company will better memorise information on a given product or place. The study tackles the issue of influencing various senses of the customers. What is more, the author presents the results of her own research. The research concerns the perception the customers have of different forms of sensory marketing. It was carried out in front of a shopping mall. The respondents had difficulties in identifying a specific place where they encountered the impact on different senses. The respondents had the greatest difficulty with specifying where taste is used, claiming that the most noticeably used sense is smell. As it stems from the declarations of the respondents, the brands associated with smell are more memorable than those associated with other elements of sensory marketing.